Prevalence of major adversecardiovascular events (MACEs) post angioplasty-HUSM Experience - Ng Seng, Loong (2008)
The primary objective of this study was to determine the prevalence of major adverse cardiovascular events (MACEs) in patients undergoing PCI in our cardiology unit in Hospital Universiti Sains Malaysia (HUSM). The second objective was to have a baseline demographic and angiographic data of the patients who had undergone PCI aswell as comparison of association between independent variables with MACEs. Risk factor control in terms of diabetic and lipid control was also analysed during clinic follow-up A total of 240 patients who underwent coronary angioplasty with stent placements were recruited into this prospective cohort study 21 patients (8.9 %) had MACEs post PCI. 5 patients had drop out from the study during follow-up. 2 variables were significantly associated with MACEs post PCI using Chi-Square test including two vessel residual disease (p<O.OO 1) and right coronary artery disease(RCA) involvement (p=0.004). Multivariate analysis maintained the association of the 2 variables including two vessel residual disease (p=0.052, adjusted OR 2.55 95% Cl 0.99-6.58) and RCA involvement (p=0.026, adjusted OR 5.53 95% CI 1.22-24.96) Multivariate analysis also identified higher HbAl C had significant association with MACEs (p=O.Oll, adjusted OR 1.93~ 95% Cl1.16-3.20) Patients who were diabetics or had high LDL-Cholesterol (LDL-C) prior to coronary angioplasty had significant improvement in metabolic risk control including reduction in HbAIC (p=0.002) and LDL-C (p<O.OOI). Furthermore, 55.7% of our hyperlipidaemic patients managed to achieve targeted LDL-C of <2.6mmol/l Conclusion: This study has shown that the prevalence of MACEs in patients undergoing PCI was not high in HUSM. Residual two vessel disease, RCA involvement and higher HbAl C were highly predictive of increased risk for MACEs post PCI. This group of patients may benefit from earlier reangiographic studies, staged revascularization therapies and more aggressive control of metabolic risk factors.